Cirrhotic Ascites management via procalcitonin level and a new approach B-mode gray-scale histogram - Şahintürk, Yasin; Çekiç, Bülent; Zorlu Görgülügil, Gizem; Akbay Harmandar, Ferda; Uyar, Seyit; Çekin, Yeşim; Hilmi Çekin, Ayhan (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To determine the role of serum procalcitonin levels and ascites/subcutaneous echogenicity ratio (ASER) in predicting ascites infection in hospitalized cirrhotic patients. Materials and Methods: A total of 50 patients hospitalized because of cirrhosis-related ascites were included in this study. In these patients, 44% of ascites were infected (peritonitis), whereas 56% of ascites were sterile. These two groups were compared in terms of procalcitonin levels and ASER for predicting ascites infection. Receiver operating characteristic (ROC) curves were used to evaluate the diagnostic performance of ASER, and the predicting outcome of ASER was compared with procalcitonin levels. Results: The ASER values of the patients with the diagnosis of infected ascites were significantly higher than in those with the diagnosis of sterile ascites (p<0.001). ROC analysis was performed to determine the diagnostic ASER value for infected ascites. An ASER greater than 0.0019 determined peritonitis with 95.5% sensitivity and 100% specificity. A procalcitonin level greater than 0.05 determined peritonitis with 86.4% sensitivity and 75% specificity. Using ROC analysis, an ASER greater than 0.0019 [area under curve (AUC): 0.974, 95% confidence interval (CI) (0.884–0.999, p<0.001)] was a significantly better diagnostic marker than a procalcitonin level >0.5 mg/dL [AUC: 0.860, 95% CI (0.884–0.999, p<0.001) (p<0.045)]. Conclusion: According to our findings, the determination of ASER and serum procalcitonin levels seems to provide satisfactory diagnostic accuracy in differentiating ascites infections in hospitalized cirrhotic patients. ASER values significantly differentiate ascites infections better than procalcitonin levels.